نحو نموذج مقاصدي لشركات توظيف الأموال = Towards Maqasidi framework for money-investment companies - Abdul Raof, Rehab Soliman; Ibrahim Mohamed, Hossam El Din; Zakaria, Mohamad Sabri (IIUM Press, International Islamic University Malaysia, 2020)
تناول البحث مسألة شركات توظيف الأموال -كإحدى آليات الاستثمار- التي تعرضت لمشكلة غلقها وتصفيتها، وإشكالية محاولة إحيائها؛ فأبرز البحث أهمية تأسيس مثل هذه الشركات، وتجارب توظيف الأموال عند المسلمين وغيرهم، وأهم انجازاتها المقاصدية، وأهم السلبيات التي وقعت فيها، ثم تطرق إلى كيفية إنجاح تطويرها وإحيائها بالحديث عن إخضاعها لأحكام الشريعة الإسلامية والقواعد القانونية والاقتصادية. وتبرز أهمية البحث في كونه يمس قضية شرعية واقتصادية تختص بتوظيف أموال الفئات التي لا تجيد إنماء أموالها بالآليات الشرعية. ولقد انتهجت الباحثة منهج الاستقراء فاطلعت على كثير من المراجع التي تناولت نفس الموضوع، واتبعت المنهج التحليلي في وصف وتحليل ما حصلت عليه من معلومات؛ حيث توصلت إلى أهمية الاستثمار في شركات توظيف الأموال في مجالات متنوعة، وإلى تكييفها الشرعي من خلال عقود المضاربة والمزارعة، وإلى ضرورة حوكمتها بالقانون وقواعد الاقتصاد. وأوصت الباحثة بإنشاء هيئات رقابية شرعية وقانونية واقتصادية تشرف على شركات توظيف الأموال المطورة. ********************************************************************************* This research discusses the issue of money-investment companies as one of the investment mechanisms, which were previously shut down, it also discusses the issue of attempting to revive it; the research sheds a light on the significance of those companies,the experiences of muslims and non-muslims of employing money, and the maqasidic benefits in addition to its shortfalls. Later on, the research suggested that through adhering to Shariah rulings, legal and economic principles, it is possible for such companies to revive, succeed, and develop themselves. The significance of this research lies in the fact that it is an Islamic, legal and economic issue concerning employing the money of the communities that are not able to do so through lawful (Islamic) mechanisms. The researcher applied the inductive and analytical method, by looking at various scientific references that discuss the subject of research, then demonstrating the information collected and analysing it, concluding on the importance of diverse investments in money-employing companies, enabling its lawful adaption through Mudarabah and Muzaraah contract, and emphasizing on the importance of law and economic principles throughout the process. Finally,the researcher recommended the creation of an Islamic, economic, and legal organization for monitoring the companies of money-investment.